Pengelolaan Waktu dalam Pendidikan Islam - Ahmad Sabri; Hidayati Hidayati; Rahmat Hidayat; Ridhatul Husna; Elfim Falahul Putra (Journal on Education, 2022)
Time (temporal dimension) has two meanings, namely denotative meaning and connotative meaning. Denotative meaning of time is a unit: seconds, minutes, hours, days, weeks, months, years, centuries and others. While the connotative meaning of time is time as a concept of achieving change in human activity. The change is expected to be a change for the better. For changes to occur for the better, human awareness is needed in interpreting events. This is known as the concept of learning from experience. Every event is a learning process, so that from this event it will change people who can interpret it. But for people who can't interpret it, events will just take place. Therefore, the meaning of the concept of time in an organizational context is called time management. To see how the conception of time management in Islamic education